Getting to Know Freelance: Opportunities and Challenges for Students - Sagala, Hotdiana; Agnes Anggriani Lumban Gaol; Meisy Priscilia Siahaan; Ros Jentri Maharani Guru Singa; Yolanda Br Sihotang (ROE: Research of Economics and Business, 2025)
The freelance phenomenon among students is growing rapidly along with advances in technology and increasingly easier internet access. Freelancing offers time flexibility that allows students to work while. In addition, working as a freelancer provides rhe opportunity to hone skills appropriate to your field of study, expand your professional network, and earn additional income. This research uses qualitative methods with interviews and observations to explore the factors behind students choosing freelance and its impact on their studies. The research result show that the main factors behind students becoming freelancers are flexibility pf working hours, opportunities to improve skills, and additional income. However, this phenomenon also has negative impacts, such us lack of focus on lectures and physical stress caused by fatigue. This research provides insight into to challenges and opportunities students face in the world of freelancing, and how they can take advantage of these opportunities.